La capacidad prospectiva y de visualización del escáner láser 3D aplicado al plan de conservación preventiva del conjunto cerámico, piedra y hierro de Antoni Gaudí y Josep María Jujol en la catedral gótica de Mallorca - Juan Antonio Ruiz; Simón Garcés; Mercè Gambús; Catalina Mas; Francisco J. Perales; Xisco Ponseti (Virtual Archaeology Review)
In this work it is presented the prospective and visualization efficiency of the 3D laser scanner as a tool applied to the elaboration of a preventive conservation plan of the ceramic done by Antoni Gaudí and Josep Maria Jujol in the gothic cathedral of Mallorca .The usage of this technique has enabled its investigation regarding digital information storage and metrology of the whole surface and plastic elements in it. This ways it is determined the creation of a multidisciplinary and interactive database with documental, technical and prescriptive content in order to compose the preventive conservation plan.